Upaya Kepala Madrasah dalam Meningkatkan Kinerja Guru - Yati Maryati; Syarwani Ahmad; Nazaruddin Nazaruddin (Journal Of Administration and Educational Management (ALIGNMENT), 2023)
This study aims to answer problems related to the efforts of madrasah heads in improving teacher performance. This research uses a qualitative approach with a descriptive type of research. Data collection techniques: Observation, interviews and documentation. Data analysis techniques: data collection, data reduction, data presentation, and drawing conclusions. Research Results: The efforts of the head of madasah in improving teacher performance in Madrasah Ibtidaiyah (MI) Al Hijriyah Prabumulih city are carried out through attendance, motivating teachers to always maintain sincerity in teaching, giving awards, restoring the spirit of teachers through madrasah family gatherings at the home of teachers / employees, holding study tours at the end of the year, holding iftar together every month romadhon, improving the knowledge of teachers by sending teachers to follow Training training, which is held in the city and in the province, sends teachers to participate in the Subject Teacher Deliberation (MGMP) throughout the city of Prabumulih or in Madrasah. The teacher's performance is already good. In conclusion, the madrasa head's efforts to improve teacher performance have been quite good Keywords: Head of Madrasah, Teacher Performance.